Two new species of Seira Lubbock (Collembola, Entomobryidae, Seirini) from South Brazil - Cipola, Nikolas Gioia; de Morais, José Wellington; Bellini, Bruno Cavalcante (Zootaxa, 2014)
Two new species of Seira, Seira tinguira sp. nov. and Seira paulae sp. nov. from Atlantic Rainforest Phytogeographic Domain in Paraná State, southern Brazil, are described and illustrated, with dorsal chaetotaxy labeled in detail. The general morphology of S. tinguira sp. nov. resembles S. frater (Bonet) and S. oceanica Yosii, however differs by chaeta Pa4 present in head, three extra macrochaetae (m1i2, p1i2 and one extranumerary) in mesothorax; four (a3, p2e, p2ea and a4) in metathorax; one (m3ep) in the second abdominal segment , among other morphological features. Seira paulae sp. nov. is similar to S. atrolutea (Arlé) in body colour, however dorsal chaetoxy resembles S. mendoncea Bellini & Zeppelini and S. ritae Bellini & Zeppelini. On the other hand, the new species clearly differs from other similar taxa by the presence of cephalic macrochaeta M2; three macrochaetae (M2, M1 and M2i) in mesothorax and p2p as microchaeta; one extra macrochaeta (p1i) in metathorax and two (a1 and p2ea) as macro or microchaetae; macrochaeta m3ep missing in the second abdominal segment; macrochaeta am6 present in the third abdominal segment among other features. Seira tinguira sp. nov. was found in different habitats of Paraná State while S. paulae sp. nov. was recorded only in its type locality. A distribution map is provided for both species. With the presented description there are now four recorded species of Seira from south Brazil.